Relative mRNA expression of CRBP IV gene and its association with layer economic traits in Rhode Island Red chicken - SAHU, AMIYA RANJAN; KUMAR, SANJEEV; JAIN, SONU KUMAR; RAJ, R CHETHAN (The Indian Journal of Animal Sciences, 2020)
Cellular retinol-binding protein (CRBP) IV gene plays an important role in absorption, transport, metabolism and homeostasis of retinol (Vitamin A) and its derivatives. Vitamin A plays vital role in ovarian follicular growth, oviduct and uterine environments, embryo and its development, and oocyte maturation. Present investigation was carried out in Rhode Island Red (RIR) chicken to assess relative mRNA expression of CRBP IV gene in kidney, liver and oviduct tissues, collected from 12 birds at 40 weeks of age from four different egg production-body weight groups, viz. high egg production-high body weight (HEP-HBW), high egg production-low body weight (HEP-LBW), low egg production-high body weight (LEP-HBW) and low egg production-low body weight (LEPLBW), using qRT-PCR method. Data on body weight at 20 weeks of age (BW20) and layer traits, viz. age at sexual maturity (ASM), egg weight at 28 (EW28) and 40 (EW40) weeks and egg production up to 40 weeks of age (EP40) were analyzed by LS ANOVA taking sire as random and hatch as fixed effects. LS means of ASM, BW20, EW28, EW40 and EP40 were 135.19±1.15 days, 1347.13±15.28 g, 42.49±0.27 g, 48.19±0.42 g and 124.55±1.94 eggs, respectively. Expression data was analyzed by LS ANOVA using SAS. The basal mRNA expression of CRBP IV gene differed significantly among different egg production-body weight groups in kidney only. The 40-ΔCt values of mRNA expression levels of CRBP IV gene in the four groups were 35.81±1.60, 29.49±1.60, 32.16±1.60 and 39.02±1.60, respectively. Significantly lower expression was observed in HEP-LBW group. Similarly, tissues differed significantly for the CRBP IV gene expression. The 40-ΔCt values of mRNA expression levels of CRBP IV gene in kidney, liver and oviduct were 34.12±0.87, 31.67±0.87 and 37.97±0.87, respectively. Highest expression was observed in oviduct. The study generated significant information on basal mRNA expression of CRBP IV gene in poultry which may have great potential for use in selection for higher reproductive efficiencies.